2020
DOI: 10.3389/fnagi.2020.580853
|View full text |Cite
|
Sign up to set email alerts
|

Different Perivascular Space Burdens in Idiopathic Rapid Eye Movement Sleep Behavior Disorder and Parkinson’s Disease

Abstract: Background: Excessive aggregation of α-synuclein is the key pathophysiological feature of Parkinson's disease (PD). Rapid eye movement sleep behavior disorder (RBD) is also associated with synucleinopathies and considered as a powerful predictor of PD. Growing evidence suggests the diminished clearance of α-synuclein may be partly attributable to poor interstitial fluid drainage, which can be reflected by magnetic resonance imaging (MRI)-visible enlarged perivascular space (EPVS). However, the effect of MRI-vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 66 publications
0
20
1
1
Order By: Relevance
“…Our population‐based findings seem inconsistent with previous clinical studies in patients with sleep or neurological disorders, that predominantly report an association of poor sleep across different characteristics with higher PVS load (Berezuk et al, 2015; Opel et al, 2019; Si et al, 2020; Song et al, 2017; Wang et al, 2020). Noteworthy, two studies from one population‐based cohort also mostly reported null findings (Del Brutto et al, 2019, 2020).…”
Section: Discussioncontrasting
confidence: 99%
“…Our population‐based findings seem inconsistent with previous clinical studies in patients with sleep or neurological disorders, that predominantly report an association of poor sleep across different characteristics with higher PVS load (Berezuk et al, 2015; Opel et al, 2019; Si et al, 2020; Song et al, 2017; Wang et al, 2020). Noteworthy, two studies from one population‐based cohort also mostly reported null findings (Del Brutto et al, 2019, 2020).…”
Section: Discussioncontrasting
confidence: 99%
“…In a recent MRI study, patients with iRBD showed significantly higher enlarged perivascular space burdens than those with PD. As the disease progressed, poor perivascular space drainage caused increased deposition of metabolites and α‐synuclein aggregation, which may obstruct the perivascular drainage systems 20 18 .…”
Section: Discussionmentioning
confidence: 99%
“…Patients with iRBD, especially men aged >50 years, will show conversion to α‐synucleinopathy disease, with a mean interval for conversion from the time of RBD onset being ~10 years, and the average annual risk of neurodegeneration being 8% 16,18,19 . Recent study also suggested that sleep disruption during REM sleep and neuroinflammation may lead to increased metabolite deposition and α‐synucleinopathy aggregation 20 …”
Section: Introductionmentioning
confidence: 99%
“…The results of studies assessing structural and functional MRI (fMRI) studies are summarized, in chronological order, in Table 4 [ 163 , 164 , 165 , 166 , 167 , 168 , 169 , 170 , 171 , 172 , 173 , 174 , 175 , 176 , 177 , 178 , 179 , 180 , 181 , 182 , 183 , 184 , 185 , 186 , 187 , 188 , 189 , 190 , 191 , 192 , 193 , 194 ]. These include sudies of gray matter volume (GMV), cortical thickness, diffusion tensor imaging, dorsal nigral hyperintensity (DNH), neuromelanin-sensitive structural and diffusion MRI, and functional MRI.…”
Section: Structural and Functional Magnetic Resonance Imaging (Mri) Studiesmentioning
confidence: 99%
“…A recent study described higher burdens of EPVS in the centrum semiovale, basal ganglia, substantia nigra, and brainstem of iRBD patients in comparison with PD patients and controls, being higher EPVS in the centrum semiovale and the brainstem as independent risk factors for iRBD [ 185 ].…”
Section: Structural and Functional Magnetic Resonance Imaging (Mri) Studiesmentioning
confidence: 99%